Migraine and restless legs syndrome – is there an association? - Bučaitė, D.; Normantas, J.; Žemgulytė, G. (Neurologijos seminarai, 2023)
Migraine and restless legs syndrome are diseases that disturb the normal quality of human life. Moreover, comorbidity of these disorders determines even more difficult condition of the patients. Migraine is a headache that can cause severe throbbing pain, usually on one side of the head, and it is often accompanied by nausea, vomiting, and extreme sensitivity to light and sound. Migraine is one of the reasons that can cause unhealthy sleep, and if sleep is disturbed, this leads to the provocation of migraine attacks. Sleep disorders have various clinical manifestations, one of which is restless legs syndrome. It is a neurosensory impairment which is characterized by an unrelenting urge to move the legs that occurs or worsens at rest. For this reason, patients may complain of impaired sleep. Although the relationship between migraine and restless legs syndrome and their pathogenesis is not fully understood, current research suggests that these diseases may be related. People with restless legs syndrome are 1.23 to 2.65 times more likely to develop migraine attacks. It is believed that the occurrence of both diseases is determined by several pathophysiological factors, such as the activity of the dopamin- ergic system, iron deficiency, genetic predisposition, and changes in the gray matter of the brain. Although the association between restless legs syndrome and migraine is being investigated, the predominant pathophysiological link has not yet been established. Separate treatment of these diseases has been known for a long time. The principle of migraine treatment is to suppress pain and reduce the frequency of attacks. Treatment for restless legs syndrome is based on the relief of symptoms. Unfortunately, a common treatment for both diseases in relation to each other has not yet been approved. Because of the similar pathophysiology of these disorders, drugs that affect the dopaminergic system (e.g., pramipexole) are currently being investigated in order to relieve the symptoms of restless legs syndrome and migraine attacks.